2022
DOI: 10.1128/mbio.01648-22
|View full text |Cite
|
Sign up to set email alerts
|

Single Seed Microbiota: Assembly and Transmission from Parent Plant to Seedling

Abstract: Seeds are key components of plant fitness and are central to the sustainability of the agri-food system. Both the seed quality for food consumption and the seed vigor in agricultural settings can be influenced by the seed microbiota.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 67 publications
4
47
0
Order By: Relevance
“…This variability in the assembly of seed microbiota has been reported by different studies and can be observed even at the single‐seed level (e.g. 2–28 bacterial ASVs per oak seed or 1–45 bacterial ASVs per bean seed) (Abdelfattah et al ., 2021; Chesneau et al ., 2021). However, the variability observed in this meta‐analysis also could be partly methodological because of the variable number of seeds used in different samples to characterize seed microbiota (from one to 1000 seeds).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This variability in the assembly of seed microbiota has been reported by different studies and can be observed even at the single‐seed level (e.g. 2–28 bacterial ASVs per oak seed or 1–45 bacterial ASVs per bean seed) (Abdelfattah et al ., 2021; Chesneau et al ., 2021). However, the variability observed in this meta‐analysis also could be partly methodological because of the variable number of seeds used in different samples to characterize seed microbiota (from one to 1000 seeds).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this meta‐analysis included mainly seed microbiota characterization from multiple seeds (> 3 seeds in sample) with > 1000 reads. More work is needed at the single‐seed level (Abdelfattah et al ., 2021; Bintarti et al ., 2021; Chesneau et al ., 2021) to assess seed‐to‐seed variation and the proportion of seeds that do not have detectable microbiota (i.e. sterile seeds) (Newcombe et al ., 2018; Ridout et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A finer clustering method may be better suited to studying the transmission of seed-associated microbes into the spermosphere since genotypes originating from the seed may be grouped within 97% OTUs originating from the soil. We recognize microbes originating from the seed can colonize seedlings and other plant organs, which can alter plant health (Bintarti et al 2022b; Bintarti et al 2022a; Chesneau et al 2022; Chesneau et al 2020; Johnston-Monje et al 2016; Mitter et al 2017; Rochefort et al 2021; Shade et al 2017; Simonin et al 2022). For example, it was recently demonstrated that crop flowers sprayed with a beneficial bacterium can colonize endosperm and transmit to germinating seeds (Mitter et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The spermosphere represents a critical zone for establishing vertically inherited seed microbes, and horizontal interactions between soil and seed-associated microbes (Chesneau et al 2022; Chesneau et al 2020; Rochefort et al 2021; Shade et al 2017; Simonin et al 2022). The outcome of these interactions can affect the life or death of the plant soon after sowing seeds (McKellar and Nelson 2003; Windstam and Nelson 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, seed microbiota functions should be considered: i.e. ecology, developmental stages, shaping of the core microbiota, vertical transmission [ 41 , 137 , 189 ], and seed-to-seed cycle [ 15 ]. Finally, an unexpected lack of reports on the effects of Arabidopsis microbiota/microbiome in issues such as nitrogen limitation [ 94 ], or plant–insect (nematode)-microbe interactions, is clearly a call for new studies.…”
Section: Concluding Remarks and Future Research Needsmentioning
confidence: 99%